Impact of Economic Growth, Energy Consumption, and Industrialization on CO2 Emissions: Evidence from Somalia - Sheikh Ali, Ali Yassin; Abdi Dhiif, Abdirahman (International Journal of Economics and Financial Issues, 2025)
This study analyzes the influence of economic growth, energy consumption, and industrialization on CO2 emissions in Somalia, employing time series data from 1990 to 2019 and utilizing the Autoregressive Distributed Lag (ARDL) model to assess both short- and long-term interactions. This research offers empirical insights into the contribution of Somalia’s emerging economy and limited industrialization to environmental deterioration. The results indicate that economic expansion and energy usage are the major contributors to CO2 emissions in Somalia. A 1% increase in GDP per capita results in a 0.80% increase in CO2 emissions, demonstrating a strong correlation between economic growth and environmental deterioration. A 1% increase in energy consumption leads to a 0.95% rise in CO2 emissions, underscoring the nation’s significant dependence on fossil fuels and suboptimal energy utilization. Nonetheless, industrialization does not demonstrate a statistically significant effect on CO2 emissions, indicating that Somalia’s industrial sector is undeveloped and has not substantially contributed to pollution levels. The short-run dynamics indicate that energy consumption significantly and immediately affects CO2 emissions, but economic expansion does not have a direct short-term influence. The error correction term (ECT = −0.2655, P < 0.01) indicates that deviations from long-run equilibrium rectify at a rate of 26.55% annually, so affirming the stability of the link among economic development, energy consumption, and environmental deterioration. These findings highlight the pressing necessity for Somalia to implement sustainable energy regulations, enhance industrial efficiency, and limit CO2 emissions. Policy proposals encompass investing in renewable energy, enhancing environmental governance, and incorporating green industrial practices to reconcile economic development with environmental sustainability. This study offers essential information for policymakers seeking to formulate sustainable economic policies while alleviating climate change effects.